PERAN SISTEM PENGENDALIAN INTERNAL PEMBERIAN KREDIT DALAM MEMINIMALISASI NON PERFORMING LOAN PADA PT BANK MITRANIAGA, Tbk - Retno Martanti Endah Lestari; Masruroh masruroh (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2015)
The one of the main business of banks is give a credit that generate revenue for the company, but on the other hand lending has risks. The risk is the emergence of NPL (Non Performing Loan) or often referred to as bad credit. The higher non-performing loans of a banking company will affect the health of banks. It required a system of internal control lending is effectively enforced in order to assist the company in order to minimize the Non-performing Loan. This study is to explain the role of the internal control system of credit in minimizing non-performing loans at PT Bank Mitraniaga, Tbk. by using primary data and secondary data. The analytical method that used is a qualitative and quantitative descriptive statistics. These results indicate that the correlation analysis values obtained significant correlation of -0.844 and 0.000, it could mean that the internal control system of crediting a significant negative effect on non-performing loans at 5% degree of confidence. Koefisisen Value Determination (Kd) of 71.3% means that the role of the internal control system of credit to non-performing loans amount to 71.3%, while the remaining amount 28.7% is explained or influenced by other factors that not examined such as external factors, customer internal factors, and factors of business failure.Keywords: Internal Control Systems of Credit and Non Performing Loan.